2009
DOI: 10.1007/s11104-009-0130-y
|View full text |Cite
|
Sign up to set email alerts
|

Root morphology and effects on soil reinforcement and slope stability of young vetiver (Vetiveria zizanioides) plants grown in semi-arid climate

Abstract: Currently used in many countries in the world, vetiver grass (Vetiveria zizanioides) applications include soil and water conservation systems in agricultural environment, slope stabilization, mine rehabilitation, contaminated soil and saline land remediation, as well as wastewater treatment. The root system morphology of vetiver was investigated in a small plantation growing on abandoned marl terraces in southern Spain. Root distribution with depth, laterally from the plant, as well as root parameters such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
3
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 28 publications
7
73
3
7
Order By: Relevance
“…From the regression analysis between tensile strength and root diameter, it can be observed that the tensile strength decreased with increasing root diameter which is in line with the previous root studies conducted by [2,4]. According to [5], during soil shearing, the finer and thinner roots that have high tensile strength would slip while the thicker roots with lower tensile strength would break.…”
Section: Tensile Strengthsupporting
confidence: 85%
“…From the regression analysis between tensile strength and root diameter, it can be observed that the tensile strength decreased with increasing root diameter which is in line with the previous root studies conducted by [2,4]. According to [5], during soil shearing, the finer and thinner roots that have high tensile strength would slip while the thicker roots with lower tensile strength would break.…”
Section: Tensile Strengthsupporting
confidence: 85%
“…Assuming that plant roots provide additional cohesion to the soil as a function of the vegetation type (e.g. Mickovski and van Beek 2009;Burylo et al 2011), the calibration has been iterated until a minimum number of cells resulted as unstable before the beginning of the event. On the basis of the land-use map, the cohesion then varies between 4.5 kPa (in the case of recently abandoned terraces, where the vegetation is sparse) to 6 kPa, in correspondence of forest and scrubland areas (Table 2).…”
Section: Evaluation Of Trigrs Input Parameters and Assumptions In Thementioning
confidence: 99%
“…This is particularly true for small diameter roots which can be considered as flexible reinforcements Mickovski et al, 2007), and which provide ductility for the root-soil continuum , reaching the peak strength at high strains (e.g. Mickovski et al, 2007;Mickovski and van Beek, 2009). …”
Section: Strength Quiredmentioning
confidence: 99%
“…The study site is located near Almudaina, Spain (X=729275 Y=4293850 and Z=480 m on UTM 30 s) and comprises approximately 2.0 m high slopes with overall slope angles ranging between 45° and 70°. The slope length was approximately 60 m, and long term monitoring recorded potential instability connected to runoff and soil slippage after intense rainfall events (Mickovski and van Beek, 2009). The runoff from the slope contributed to the undermining of the slope toe where the progressive failure initiated before migrating up the slope and resulting in bulging mid-slope and soil mass depositing at the toe ( Figure 5).…”
Section: Case Study (Model Validation)mentioning
confidence: 99%
See 1 more Smart Citation